Measurement and calculated dose in breast phantom - Rahman, Siti Hajar Abdul (2004)
The aim of this study was to compare the dose calculated by NUCLETRON PLATO treatment planning computer with thermoluminescence dosimeter (TLD) measurement in breast cancer radiotherapy. The absorbed dose distribution for one-field technique and two-field techniques were discussed. The study was done by comparing interest point dose values calculated by treatment planning computer with dose values measured by LiF TLDs. Utilizing an anthropomorphic phantom, TLDs were placed inside a breast phantom and were irradiated with 6MV SIEMENS MEVATRON linear accelerator. One-field technique and two-field techniques were used for the irradiation. Readings from irradiated TLDs were analyzed. Absorbed dose distributions for one-field and two-field techniques were obtained from the computer. Based on the results, dose values for the four points of interest in which calculated by the treatment planning computer and measured by TLDs were within 13%. Inexact location of points of measurement during phantom's set up caused large deviation between the calculation and TLD measurement. TLD measurement and the calculation do not comply to ICRU recommendation.